Postmortem computed tomography and postmortem computed tomography angiogram in sudden natural death - Abdul Rashid, Saiful Nizam (2020)
Introduction Post-mortem computed tomography (PMCT) acts as an adjunct to autopsy but with limitations in vascular and organs diagnosis. This is alleviated using postmortem computed tomography angiogram (PMCTA). Current PMCTA approaches and protocols are not based on Asian population. Whole-body PMCTA uses femoral approach while selective PMCTA uses neck approach. Whole body PMCTA using neck approach is more feasible in our mortuary. Sudden natural death is the commonest cause of natural death (COD) in Malaysia. A modified whole-body PMCTA scanning and infusion protocol based on body weight for the Asian population using the neck approach was derived and tested. Methodology A prospective, double-blinded, cross over randomized control trial study was conducted. Each subject underwent PMCT, PMCTA and finally autopsy. Watersoluble contrast media combined with Polyethylene Glycol 200 was used. The reliability of the modified protocol in terms of diagnostic value for organ and vascular pathology in comparison to autopsy, diagnosing and comparing the COD as well as complications were documented. The confidence level (CL) in formulating the COD, PMCTA helps in the final COD compared to PMCT and decision on autopsy based on PMCT/PMCTA findings were assessed. Results and Discussion 60 cases recruited with 46 males and 14 females (22-75 of age, mean of 45.6). 32 Malaysian and 28 non-Malaysian with Asian ethnicities, majority were Muslim. The "embalming effect" due to excessive amount of contrast media, higher infusion rate and pressure using the recommended protocol was documented at the initial stage of the study. This was eliminated by decreasing the amount of CM based on body weight and gradually increasing the rate and pressure during infusion. The whole body was analyzed based on anatomical systems and PMCT/PMCTA findings were comparable to autopsy. Similarity coefficient (SC) value of 0.876 for all 3660 variables analyzed and statistically significant showed a strong correlation. The vascular system has the strongest correlation. The commonest COD was cardiovascular death. 78.3% matched, 15.0 % minor and 6.67% major COD discrepancies between radiologists and pathologists. Strong relationship for both radiologists (SC :0.867 to 0.883) but slightly lower when compared to pathologists (SC value: 0.767). Hypothesis testing revealed significant results and concluded that there is relationship or similarity conclusion on COD between radiologists and pathologists. Radiologists CL was generally lower compared to pathologists. Highest CL was in diagnosing vascular pathologies. PMCTA increased their CL and helped in their COD compared to PMCT alone. Majority still needs full or limited autopsy. Conclusion The new modified PMCTA protocol for the Asian population using the neck approach has been proven scientifically and statistically with high diagnostic value and promising results. Radiologists COD based on PMCT/PMCTA was comparable to autopsy especially in vascular-related pathology. The role of Forensic Imaging in Malaysia stays as an adjunct to autopsy and not to completely replace it with high potential for limited autopsy in the future.